The impact of bleeding complications in patients receiving target-specific oral anticoagulants: A systematic review and meta-analysis - Chatree Chai-Adisaksopha (2018)
© 2014 by The American Society of Hematology. Vitamin Kantagonists (VKAs) have been the standard of care for treatment of thromboembolic diseases. Target-specific oral anticoagulants (TSOACs) have been developed and found to be at least noninferior to VKAs with regard to efficacy, but the risk of bleeding with TSOACs remains controversial. We performed a systematic review and meta-analysis of phase-3 randomized controlled trials (RCTs) to assess the bleeding side effects of TSOACs compared with VKAs in patients with venous thromboembolism or atrial fibrillation. We searched MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials; conference abstracts; and www.clinicaltrials.gov with no language restriction. Two reviewers independently performed study selection, data extraction, and study quality assessment. Twelve RCTs involving 102 607 patients were retrieved. TSOACs significantly reduced the risk of overall major bleeding (relative risk [RR] 0.72, P < .01), fatal bleeding (RR 0.53, P < .01), intracranial bleeding (RR 0.43, P < .01), clinically relevant nonmajor bleeding (RR 0.78, P < .01), and total bleeding (RR 0.76, P < .01). There was no significant difference in major gastrointestinal bleeding between TSOACs and VKAs (RR 0.94, P 5 .62). When compared with VKAs, TSOACs are associated with less major bleeding, fatal bleeding, intracranial bleeding, clinically relevant nonmajor bleeding, and total bleeding. Additionally, TSOACs do not increase the risk of gastrointestinal bleeding.